Research advances in internal tooth resorption - XU Wenkai, ZHU Jing, HUANG Zhaoyang, LIANG Guangzhi (精准医学杂志)
As a rare pulp lesion, internal tooth resorption often has no obvio clinical symptoms and signs and is only accidentally identified during medical imaging examination, and its diagnosis and treatment have always been a difficult issue for dentists. Misdiagnosis or missed diagnosis of this disease can lead to the failure in root canal therapy and even root fracture and premature tooth loss. This article reviews the etiology, diagnosis, and treatment of internal tooth resorption and summarizes the latest research advances, in order to provide theoretical support and treatment strategies for dentists in the diagnosis and treatment of internal tooth resorption in clinical practice and further improve the success rate of diagnosis and treatment.